Pharmaceutical Intervention: description of the role of the clinical pharmacist in intensive care units - Stéphanie L. COLIN; Camile NUTTI (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To describe and analyze the profile of pharmaceutical interventions by identifying and classifying drug-related problems (DRP) and carrying out pharmaceutical interventions in order to highlight the importance of the intensivist clinical pharmacist. Methodology: Cross-sectional, descriptive and retrospective study of the results of the pharmacotherapeutic monitoring service aimed at critically ill patients admitted to the Cardiological and General ICUs of a state public hospital. Data were collected from September 1, 2020 to March 30, 2021, through an institutional pharmacotherapeutic follow-up report and the DRPs identified, quantified and classified according to the Pharmaceutical Care Network Europe. The drugs involved in the problems were categorized using the Anatomical Therapeutic Chemical. Results: A total of 331 patients were followed up during the study period, with the identification of 181 MRPs. Of these, most were related to adverse event (possibly) representing (34.8%) and unavailability or inadequacy of pharmaceutical presentation (29.8%). The main causes of DRP identified were inadequate pharmaceutical form (19.3%) and unavailable prescribed medication (19.3%). Most of the problems (24%) were related to the class of drugs that act on the nervous system and the class of general anti-infectives for systemic use (23%). Of the recommendations made for the optimization of pharmacotherapy, 98.3% were accepted, with the suggestion of changing the pharmaceutical form prevailing (22.1%). Conclusion: The high acceptability of the interventions suggested by the intensivist clinical pharmacist reinforces the importance and need for the clinical services provided by this health professional.